Minimizing EFL Learners’ Speaking Anxiety in the Post-Pandemic Era - Hilda Afidawati; Farouk Imam Arrasyid; Listiana Ikawati (JEELS (Journal of English Education and Linguistics Studies), 2024)
The COVID-19 pandemic, which lasted for more than 2 years, had a tremendous impact in Indonesia. One of its impacts on the education sector that is still affecting the post-pandemic period is learning loss. Learning loss is a phenomenon where students lose their knowledge and skills due to certain conditions. Learning loss also affects students’ psychology. In speaking learning, anxiety is one of the students' obstacles to speaking fluently. This study aimed to investigate the strategies employed by students to mitigate speaking anxiety in the post-pandemic era. The case study design was used to do an in-depth investigation of complex problems regarding students' speaking anxiety in a school. The study involved six students in grade seven at a junior high school in West Java, Indonesia, as participants. The participants selected were those representing different speaking abilities based on their speaking test results. The data was collected through semi-structured interviews. The findings show that students employ several strategies to mitigate their speaking anxiety, including preparation, relaxation, positive thinking, and peer-seeking. In other words, those strategies reflect students’ resilience to deal with learning loss in the post-pandemic era.  This study is intended to serve as a valuable resource for educators and EFL learners by providing strategies to alleviate speaking anxiety effectively.